Given sin^4 x - cos^4 x = 2sin^2 x - 1

==> We will rearrange terms.

==> sin^4 x - 2sin^2 x + 1 = cos^4 x

Now we will factor the left side.

==> (sin^2 x -1)^2 = cos^ 4 x

But we know that sin62 x = 1- cos^2 x

==> (1-cos^2 x -1 )^2 = cos^4 x

==> (-cos^2 x)^2 = cos^4 x

==> cos^2 4 x = cos^4 x

**Then, we have proved that sin^4 x - cos^4 x = 2sin^2 x - 1.....**

We have to prove : sin^4x - cos^4x = 2sin^2x - 1

Let's start from the left

(sin x)^4 - (cos x)^4

=> (sin x)^4 - [ 1 - (sin x)^2]^2

=> (sin x)^4 - 1 - (sin x)^4 + 2*(sin x)^2

=> - 1 + 2*(sin x)^2

=> 2*(sin x)^2 - 1

which is the right hand side.

**This proves that sin^4x - cos^4x = 2sin^2x - 1**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now